The African-American Minority Beyond New Racism: Post-Obama Era And The Myth Of Post-Racialism In Us Public Schools (مجلة الواحات للبحوث والدراسات, 2025)
The historic 2008 presidential election, won by Barack Obama as the first African-American president, has introduced America to the so-called post-racial era. Although concerted efforts to eliminate racism are heightening public discourse, social disparities in the field of education continue to be silenced. This paper uses critical race theory as a lens to identify the issue of racial oppression in K-12 schools. Thus, qualitative and quantitative approaches are used to explain why racism became subtler during Obama’s presidency. It aims to examine different anti-racist dialogues that may help African-Americans and whites come out of their black and white fragility, beginning with schools. To realize the aforementioned objective, it is important to ask: Why does the American system of education continue to mute social inequity in US public schools? As a matter of fact, racism is ineradicable, even though the president is black. Americans dismiss race talk and prefer to deny that there are problems with inequality due to social constraints. Keywords: African-Americans, Critical Race Theory, K-12 Schools, New Racism, Post-Racialism.